Desain Lembar Kerja Peserta Didik dengan Pendekatan Discovery Learning terhadap Kemampuan Pemahaman Konsep Matematis - Abdullah, Nur; Putra, Harry Dwi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Singaperbangsa, 2024)
The aim of this research is to design Student Worksheets (LKPD) using the discovery learning model to enable students to understand the material being studied. This research uses a design research method with three stages, namely design design, design implementation, and retrospective analysis. The instruments used in this research are LKPD design and summative tests, data analysis uses retrospective analysis by describing the results of research instruments that have been carried out by students. Design planning starts from determining goals and competencies, selecting teaching materials, creating LKPD model discovery learning, consulting with lecturers and design improvements. The application of the design is carried out during learning activities. LKPD analysis shows good things, students are able to follow and complete the learning process using LKPD, in the summative test students are able to answer the questions given with good data and steps, plus the results of learning reflection show students are happy and easily understand the concept of the material using the LKPD so that the LKPD model of discovery learning has a big role in understanding of concepts